Congenital cytomegalovirus infection. Issue 6 (June 2018) - Joseph, Amelia; Mahida, Nikunj; Clark, Gemma; Irving, William; Soo, Shiu
Abstract: Congenital cytomegalovirus is the most common intrauterine infection and the leading non-genetic cause of sensorineural hearing loss. Worldwide, the birth prevalence is estimated at 7 per 1000 with the highest rates seen in developing countries. The highest intrauterine transmission rates and risk of neurodevelopmental sequelae are associated with primary maternal infections. Transmission occurs less frequently after non primary maternal infections due to reactivation or reinfection. 10–15% of infected infants are symptomatic at birth, with neurological symptoms present in two-thirds. Infants who are asymptomatic at birth may go on to develop late neurodevelopmental sequelae, with sensorineural hearing loss being the commonest late consequence. Prenatal, neonatal and retrospective diagnosis can be challenging. Early treatment of symptomatic neonates with the antiviral drug valganciclovir can reduce the long-term neurodevelopmental sequelae. Universal or targeted screening for congenital CMV is not currently advocated. The development of an effective vaccine appears to be some years away. This review highlights the important considerations for clinicians regarding the diagnosis, investigation and management of children with possible or confirmed congenital CMV infection.